Biomechanics of accurate and inaccurate goal-kicking in Australian football: Group-based analysis - Blair, S.; Robertson, S.; Duthie, G.; Ball, K. (PLOS ONE, 2020)
Goal-kicking is an important skill in Australian Football (AF). This study examined whether kinematic differences exist between accurate and inaccurate goal-kicks and determined the relationships between technical factors and accuracy. Eighteen elite to sub-elite AF players performed 15 x 30 m goal-kicks on an AF training ground, with three-dimensional kinematics collected using the Xsens inertial measurement system (Xsens Technologies B.V., Enschede, the Netherlands). A general linear mixed modelling approach and regression-based statistics were employed to quantify differences between accurate and inaccurate goal kicks and the relationships between technical factors and accuracy. Accurate goal-kicks were characterised by a straighter approach line, with less kick-leg joint range of motion (knee and hip), lower linear velocity (centre of mass, foot speed), angular velocity (knee and shank), and less support-leg knee flexion during the kicking phase compared to inaccurate goal-kicks. At the end of the follow through, players produced greater ankle plantarflexion and a straighter-leg line in accurate goal-kicks. Findings in this research indicated that many factors interact with goal-kicking accuracy in AF, ranging from the players` approach line path, their support-leg mechanics, the kick-leg swing motion, to the final position of the kicker during their follow through.